2019
DOI: 10.7150/jca.28809
|View full text |Cite
|
Sign up to set email alerts
|

CDCA5, Transcribed by E2F1, Promotes Oncogenesis by Enhancing Cell Proliferation and Inhibiting Apoptosis via the AKT Pathway in Hepatocellular Carcinoma

Abstract: Cell division cycle associated 5 (CDCA5) is an important element for the interaction between cohesin and chromatin in interphase. It is abnormally expressed in many types of cancer and works as an indicator of poor prognosis, but little is known about its activity in hepatocellular carcinoma (HCC). In the present study, we found that the expression of CDCA5 was upregulated in HCC tissues compared to paracancerous tissues and had a negative correlation with patient survival. Cell proliferation and tumorigenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 30 publications
6
45
0
Order By: Relevance
“…A recent study shows that CDCA5 probably serves as a biomarker for the prognosis, treatment, and diagnosis for HCC [38][39][40]. It also exerts a vital part in the proliferation of HCC cells [41,42], OSCC [41,42], and bladder cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that CDCA5 probably serves as a biomarker for the prognosis, treatment, and diagnosis for HCC [38][39][40]. It also exerts a vital part in the proliferation of HCC cells [41,42], OSCC [41,42], and bladder cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Among the TFs targeted by NEIL3, E2F1 represents a key link in the cell cycle regulation network, and its aberrant expression participates in HCC occurrence and development, which also predicts the unfavorable patient prognosis [42]. As reported, E2F1, which is tightly linked to cell division cycle associated 5 (CDCA5), Sirtuin 5 (SIRT5) and other important molecules, may serve as a vital anti-apoptotic factor in liver cancer due to its ability to offset c-Myc-driven apoptosis [43,44]. As suggested in previous literature, the repressive complex, which includes the component of E2F4, is relieved by CDK upon reentry into the cell cycle; thereafter, E2F1-Sp1, which is in the form of complex E2F1-NF-Y, can be recruited to the promoter [45].…”
Section: Discussionmentioning
confidence: 92%
“…CDCA5 participated the promotion of HCC cells proliferation, migration, and invasion, palying a tumor-promotive role and being a potential therapeutic target for patients with HCC [16,17]. Besides, CDCA5 was found to be transcribed by E2F1, and could promote oncogenesis by enhancing cell proliferation and inhibiting apoptosis via the AKT pathway in HCC [18]. Another research found that increased CDCA5 expression was associated with increased tumor diameter and microvascular invasion in HCC [19].…”
Section: Discussionmentioning
confidence: 98%